Students’ satisfaction on services quality : comparison between public and private universities in Klang Valley - Nor Haniza Ishak; Zuraini Md Ali; Rodiah Zawawi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Education is able to enhance an individual’s quality of life particular in the higher education. With proper knowledge from higher education, graduate students are able to build up self-leadership, obtain better health-care, more prestigious employment and greater job satisfaction. The aim of this study is to compare the service quality between public and private university in Malaysia based on their students’ satisfaction. This is because the evaluation of service quality in universities will provide significant findings or inputs for management level in decision-making process in order to improve their services quality. Hence, the research was conducted at two selected case studies which are public and private university respectively using modified SERVQUAL approach. The target respondents of this study are undergraduate students from both universities. About 420 copies of questionnaires were distributed and collected in four selected faculties at both universities. From the results, Public University showed lowest negative gap score compared to Private University. Besides, correlation analysis also proved that there were significant relationships between service quality and student satisfaction which indicated that service quality of both university lead the student’s satisfaction. The analysis also found that there were significant relationships between interrelated factors amongst dependent variable which are five SERVQUAL dimensions. In addition, the assessments of service quality in both universities were able to provide comprehensive understanding of the students’ needs and significant inputs for improving their higher education quality. Furthermore, the findings were also able to provide comprehensive information for management level in decision-making process particularly if they are intending to implement new programmes inside their universities.